Does government support enhance the relation between networking structure and sustainable competitive performance among SMEs? - Asem Alkahtani; Norfarah Nordin; Rizwan Ullah Khan (Journal of Innovation and Entrepreneurship, 2020)
Purpose: The underlining study's main objective is to examine how networking structure (density and centrality) affects sustainable competitive performance in Pakistan's SMEs. Design/methodology/approach: Hence, small enterprises a significant source of economic development, employment, and value creation. Therefore, on the base of previous literature, we developed hypothesis related government financial support and network structure, and data collected through structured questionnaires from top management of SMEs. Findings: The results indicate that density has a positive and significant effect on sustainable competitive performance, while centrality has an insignificant impact on SCP. Furthermore, government financial support strongly and significantly supports the relation between networking structure and SCP in Pakistan. Practical implications:This research has several recommendations for the government to adequately support small enterprises because owners have a networking system at the local and international level but have a lack of environment. Originality/value:Government plays a crucial role in small- and medium-sized enterprises boost performance and economic growth because it creates employment opportunities, poverty reduction, and economic development. Nevertheless, from the last decades, due to some organizational policies and environmental flexibility, SMEs face a lot of challenges which became a barrier such as lack of government subsidies, incentives, and taxes in emerging economies. To bridge the above challenges of SMEs, the current study is conducted because before this there was no such literature who underline the current challenges in emerging economies.
Keywords: 650; Density; Centrality; Government support; Sustainable competitive performance